Evaluation of Shear Strength of Concrete Flat Plates Reinforced with GFRP Plates - Min Sook Kim; Young Hak Lee (International Journal of Polymer Science)
The shear performance of concrete flat plates with glass fiber-reinforced polymer (GFRP) plate shear reinforcement was investigated through punching shear tests. Each GFRP plate was embedded in the concrete and included openings to permit the flow of concrete during fabrication. Punching shear tests were conducted on a total of 8 specimens, and the resulting crack and fracture formations, strains, and load-displacement curves were analyzed and compared. The experimental variables considered were the types of shear reinforcement, including steel stirrups or GFRP plates, and the shear reinforcement spacing. The experimental results show that the GFRP shear reinforcement effectively increased the shear strengths of flat plates. Furthermore, the applicability of two formulas was investigated: a modified version of a shear strength formula from ACI 318-14 and the ACI 318-14 fracture prediction formula.